Evaluasi Program Pembelajaran Sebagai Upaya Peningkatan Nilai Rapor Pendidikan Tahun 2022 Di SMPN 4 Kebumen - Amin Al Adib; Zaenab Ulfah Hasanah (LPPM Universitas Proklamasi 45, 2023)
ABSTRACTObjective of this research is to describe on how to construct the students’ report card at the SMPN 4 Kebumen, Central Java, based on the learning program evaluation. This report card portrays students’ progress on understanding all school subjects. This is a descriptive-qualitative research, and we use either observation or interview as a method to collect data. When interviewing the head master, teachers and some students, we use three postulates i.e. literation, numeric, and character. Those three postulates are the crucial content of the minimum competency assessment. It means that a success student should have at least those three competencies. This research revealed that the students’ report cards have already reflected those three minimum competencies. Majority students have good literation quality, high order thinking skill and ability to apply Pancasila (Indonesian basic ideology) in their daily life.